Invisible veterans: defeated militants and enduring revolutionary social values in Dhufar, Oman - Wilson, Alice (Conflict and Society, 2019)
Those who have participated in organized political violence often develop distinctive identities as veteran combatants. But what possibilities exist to produce a veteran identity for “invisible” veterans denied public recognition or mention, such as politically repressed defeated insurgents? Everyday socializing during or after political violence can help restore social worlds threatened or destroyed by violence; an examination of “invisible” veteran defeated revolutionaries in Dhufar, Oman, shows how everyday socializing can help reproduce a distinctive veteran identity despite political repression. Ethnographic fieldwork with veteran militants from the defeated revolutionary liberation movement for Dhufar reveals that while veterans (who are a diverse group) no longer publicly reproduce their political and economic revolutionary ideals, some male veterans—through everyday, same-sex socializing—reproduce revolutionary ideals of social, especially tribal and ethnic, egalitarianism. These practices mark a distinctive veteran identity and indicate an “afterlife” of lasting social legacies of defeated revolution.
Keywords: Dhofar

Kinship and a counter‐hegemonic social order: former revolutionaries in southern Oman - Wilson, Alice (Journal of the Royal Anthropological Institute, 2020)
Les réinterprétations critiques des travaux en anthropologie de la parenté ont remis en question les idées antérieures selon lesquelles les relations de parenté reflètent et reproduisent un ordre social dominant. Pourtant, les études consacrées aux nouvelles formes de parenté tendent à montrer que celles‐ci peuvent reproduire des idées traditionnelles concernant la famille, les valeurs et les hiérarchies sociales. Pour résister aux tendances actuelles liant la parenté à une reproduction sociale conservatrice, une piste prometteuse est la meilleure compréhension des circonstances dans lesquelles les relations de parenté reproduisent un ordre social anti‐hégémonique. Parmi les anciens militants du mouvement de libération révolutionnaire, aujourd'hui vaincu, de Dufar, dans le sultanat d'Oman, les pratiques de parenté visualisent des réseaux et relations entre anciens combattants qui transgressent les hiérarchies tribales, ethniques, raciales et genrées dominantes. Ces pratiques montrent comment, même dans les circonstances peu propices de la défaite politique et de la marginalisation, les relations de parenté peuvent reproduire un ordre social anti‐hégémonique, tout en offrant une rémanence sociale à la révolution vaincue.
Keywords: Dhofar

Afterlives of Revolution: Everyday Counterhistories in Southern Oman - Wilson, Alice (Stanford University Press, 2023)
The Dhufar Revolution was fought between 1965–1976, in an attempt to depose Oman's British-backed Sultan and advance social ideals of egalitarianism and gender equality. Dhufar, the southernmost governorate in today's Sultanate, captured global attention for its revolutionaries and their liberation movement's Marxist-inspired social change. But following counterinsurgency victory, Oman's government expunged the revolution from sanctioned historical narratives. Afterlives of Revolution offers a groundbreaking study of the legacies of officially silenced revolutionaries. How do their underlying convictions survive and inspire platforms for progressive politics in the wake of disappointment, defeat, and repression?Alice Wilson considers the "social afterlives" of revolutionary values and networks. Veteran militants have used kinship and daily socializing to reproduce networks of social egalitarianism and commemorate the revolution in unofficial ways. These afterlives revise conventional wartime and postwar histories. They highlight lasting engagement with revolutionary values, the agency of former militants in postwar modernization, and the limitations of government patronage for eliciting conformity. Recognizing that those typically depicted as coopted can still reproduce counterhegemonic values, this book considers a condition all too common across Southwest Asia and North Africa: the experience of defeated revolutionaries living under the authoritarian state they once contested.
Keywords: Dhofar